Cancer Associated Viruses - Robertson, Erle S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This volume constitutes a comprehensive review of the different aspects of tumor virology 100 years after the discovery of the Rous-sarcoma virus. Its aim is to bring a greater focus on the contributions of viral agents to the development of cancer, and to create an up to date compendium of the general molecular biology of these viruses,  their gene products, and targeted functions. The content of the book comprises general chapters which tie into the many aspects of cancer-related viruses and how they contribute to cell proliferation, the genes that are responsible for driving these cancers, and their mechanisms of transmission. The book also reviews the current knowledge on the molecular biology of large DNA viruses and describes the many different pathways through which they contribute to cell proliferation. Papilloma viruses and Adenoviruses, well known to be associated with invasive carcinomas, and hepatitis viruses, HTLV and retroviruses are also discussed. This volume is dedicated to  Baruch Blumberg, an outstanding scientist and recipient of the Nobel Prize for the discovery of the hepatitis B virus, who was also the author of one of the chapters.
In Memoriam -- Preface.- Peyton Rous: A centennial tribute to the founding father of cancer virology -- Historical Perspectives of Viruses and Cancer.- Virus Mediated Cell Proliferation -- Viral Encoded Genes and Cancer -- Oncogenic Viruses and Cancer Transmission -- Overview of DNA Viruses and Cancer -- Herpesviruses and Cancer -- Lymphocryptoviruses- EBV and its role in human cancer -- LCV and RRV in nonhuman primates -- Rhadinoviruses – KSHV and associated malignancies -- RFHV and contribution to disease -- Murine herpesvirus 68 in Tumorigenesis -- Marek’s Disease Virus and T cell Lymphomas -- Polyoma Viruses and Cancer -- SV40 as a Model System for Cancer -- BK virus and Transformation -- JC virus and Transformation -- Merkel Cell Polyoma viruses -- Papilloma Viruses – HPV and BPV and Cancer.-and Cell proliferation -- Overview of Hepatitis Viruses and Cancer -- Hepadna Viruses - HBV and Hepatocellular Carcinomas -- Hepatitis C Virus and Hepatocellular Carcinomas.– Human and Animal Retroviruses: HIV-1 a Risk Factor for Malignancy -- HTLV-1 and Cell Proliferation -- HTLV-2 and Cell Proliferation -- Avian and Murine Retroviruses -- Rous Sarcoma Virus -- Mouse Mammary Tumor Viruses -- Jaagsiekte Sheep Retrovirus and Lung Cancer -- Small RNAs and their Role in Viral Mediated Cancers -- Immunodeficiency and Opportunistic Viral infections and Cancer -- Index.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.